The Polymer Melts Rheology Peculiarities - A.S. Naumenko (Механика машин, механизмов и материалов, 2008)
Rheological equation of the line polydisperse polymer in the one-dimensional asymptotic approximation is offered using statistical method to describe the melt shear flow process. The physical content of its basic characteristics is determined. The rheological equation allows explaining rather broad range of the experimentally stated peculiarities of the polymer melt shift flow.